DEVELOPMENT STRATEGY OF SEMARANG TYPICAL BATIK MSMES IN SEMARANG BATIK VILLAGE - Nurfidhah Luthfiyah; Kardoyo; Mahmud, Amir (Universitas Negeri Semarang, 2025)
Semarang Batik Village is one of the leading batik centers in Central Java, with significant cultural and economic potential. However, it continues to face challenges related to production, marketing, capital, and partnerships. This study aims to formulate development strategies for Batik Khas Semarangan MSMEs using the Business Model Canvas (BMC) framework, which comprises nine key components of a business model. A descriptive qualitative method with a case study approach was employed. Data were collected through in-depth interviews with MSME actors, direct observations, and documentation. The data were then analyzed using the Miles and Huberman interactive analysis technique and organized according to the BMC framework to produce adaptive and sustainable development strategies. The results indicate that: (1) the production strategy emphasizes preserving local batik motifs—such as Warak Ngendog—and regenerating artisans through culturally based training; (2) the marketing strategy focuses on digitalizing distribution channels and integrating cultural storytelling into promotional content; (3) the capital strategy highlights the diversification of funding sources and the strengthening of financial literacy among business actors; and (4) the partnership strategy encourages crosssector collaboration with government agencies, educational institutions, and the creative industries. Overall, the findings demonstrate the value of the BMC as an analytical tool that not only maps the internal structure of MSMEs but also supports the development of applicable, locally grounded, and market-responsive strategies.